2016
DOI: 10.1177/0969733015622059
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and patients’ perceptions of privacy protection behaviours and information provision

Abstract: These findings provide empirical data to create an ethical environment for the future, as considerable attention has been devoted to patients' rights and medical institutions' liability for providing explanations to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 22 publications
1
29
0
9
Order By: Relevance
“…In some cases, we found that the four elements of psychosocial fundamental care were only a small component of the entire tool: this is the case, for example, with the Consumer Assessment of Healthcare Providers and Systems, Hospital version (HCAHPS), in which we found, among 27 items, reference to fundamental care in only two items related to patients’ respect (Levin et al, 2017; Ng et al, 2009; Otani, Herrmann, & Kurz, 2011). For 10 other instruments, we found the same limitations (Spiritual Care Needs Inventory (SCNI‐21): Wu, Koo, Tseng, Liao, & Chen, 2015; questionnaire used by Kim, Han, & Kim, 2017; Person‐Centred Climate Questionnaire (PCQ‐P): Johnston, Gaffney, Pringle, & Buchanan, 2015; The intensive care unit psychosocial care scale (ICU‐PC Scale): Hariharan, Chivukula, & Rana, 2015; National Survey of English Inpatients: Hargreaves, Sizmur, & Viner, 2012; Chinese Comfort, Afford, Respect, and Expect scale (CARE‐C): Chung, Hsieh, Chen, Chang, & Hsu, 2018; questionnaire used by Chen & Raingruber, 2014; questionnaire used by Chaplin, Crawshaw, & Hood, 2015; Flemish Patient Survey (FPS): Bruyneel et al, 2017; Thai Nurses’ Caring Behavior Scale (TNCBS): Udomluck, Tonmukayakul, Tiansawad, & Srisuphan, 2010). Other studies, even though they did not specifically set out to investigate of the four elements of psychosocial fundamentals care, used instruments that could investigate all four elements.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In some cases, we found that the four elements of psychosocial fundamental care were only a small component of the entire tool: this is the case, for example, with the Consumer Assessment of Healthcare Providers and Systems, Hospital version (HCAHPS), in which we found, among 27 items, reference to fundamental care in only two items related to patients’ respect (Levin et al, 2017; Ng et al, 2009; Otani, Herrmann, & Kurz, 2011). For 10 other instruments, we found the same limitations (Spiritual Care Needs Inventory (SCNI‐21): Wu, Koo, Tseng, Liao, & Chen, 2015; questionnaire used by Kim, Han, & Kim, 2017; Person‐Centred Climate Questionnaire (PCQ‐P): Johnston, Gaffney, Pringle, & Buchanan, 2015; The intensive care unit psychosocial care scale (ICU‐PC Scale): Hariharan, Chivukula, & Rana, 2015; National Survey of English Inpatients: Hargreaves, Sizmur, & Viner, 2012; Chinese Comfort, Afford, Respect, and Expect scale (CARE‐C): Chung, Hsieh, Chen, Chang, & Hsu, 2018; questionnaire used by Chen & Raingruber, 2014; questionnaire used by Chaplin, Crawshaw, & Hood, 2015; Flemish Patient Survey (FPS): Bruyneel et al, 2017; Thai Nurses’ Caring Behavior Scale (TNCBS): Udomluck, Tonmukayakul, Tiansawad, & Srisuphan, 2010). Other studies, even though they did not specifically set out to investigate of the four elements of psychosocial fundamentals care, used instruments that could investigate all four elements.…”
Section: Resultsmentioning
confidence: 72%
“…Most of the studies involved patients only ( n = 36), hospitalised in different care units (e.g. cardiology n = 4; oncology and palliative care n = 11), although most studies occurred across various clinical specialities (Borhani et al, 2014; Bruyneel et al, 2017; Chaplin et al, 2015; Chochinov et al, 2016; Chung et al, 2018; Comiskey et al, 2014; Ehrlander et al, 2009; Ferri et al, 2015; Fröjd et al, 2011; Gattinger et al, 2013; Goh, Ang, Chan, He, & Vehviläinen‐Julkunen, 2015; Goh et al, 2016; Hall et al, 2013; Hargreaves et al, 2012; He et al, 2013; Kim et al, 2017; Ota et al, 2019; Otani et al, 2011; Papastavrou et al, 2012b; Periyakoil et al, 2009; Raee et al, 2017; Tauber‐Gilmore et al, 2018; Teunissen et al, 2016; Udomluck et al, 2010; Wu et al, 2015; Yousuf et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Literatürde yer alan birçok çalışmada, mahremiyet kavramının ve boyutlarının hasta ve hemşireler tarafından farklı algılandığı, mahremiyet ile ilgili tercih, düşünce ve beklentilerin değişkenlik gösterdiği görülmektedir. [14][15][16][17][18][19][20] Anthony ve Stablein, sağlık profesyonellerinin mahremiyeti; hasta bilgilerinin korunması, temel mesleki etiğin ve mesleki çalışmalarının bir parçası olarak algıladığını belirtmişlerdir. 21 Koivula-Tynnilä ve ark.…”
unclassified
“…ise iç hastalıkları ve cerrahi kliniklerinde çalışan hemşirelerin mahremiyeti korumayı önemsemelerine rağmen, mahremiyeti koruyucu davranışlarının daha az olduğunu saptamışlardır. 17 Literatürde, gelecekte hemşirelik mesleğinin birer üyesi olacak hemşirelik öğrencilerinin mah-Deniz ÖZTÜRK ve ark.…”
unclassified
“…Bu nedenle hastaların mahremiyetlerini korumak için daha güçlü tedbirlere gereksinim duyulmaktadır. (14) Hemşirelerin hasta mahremiyeti algı ve yaklaşımları ile ilgili yapılan daha önceki çalışmalar, kadın doğum, acil servis ve yeni doğan ünitesi gibi özel alanlarda gerçekleştirilmiştir. Bu nedenle, genel birimlerde çalışan hemşirelerin mahremiyete yaklaşımlarının belirlenmesine de gereksinim duyulmaktadır.…”
unclassified